2016
DOI: 10.2106/jbjs.rvw.o.00027
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Bone-Healing by Low-Intensity Pulsed Ultrasound

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Low-intensity pulsed ultrasound (LIPUS) is well-documented to enhance heal rate of fractures under a range of conditions [33]. However, closed non-displaced metatarsal fractures are expected to heal well in any case.…”
Section: Discussionmentioning
confidence: 99%
“…Low-intensity pulsed ultrasound (LIPUS) is well-documented to enhance heal rate of fractures under a range of conditions [33]. However, closed non-displaced metatarsal fractures are expected to heal well in any case.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, many are related to slower bone healing or even non-unions. There has been a recent increase in the popularity of LIPUS in the fracture/non-union setting, and a recent meta–analysis by Rutten et al [ 49 ] described that LIPUS was able to reduce the time to radiographic fracture healing. Similarly, in the setting of limb lengthening we found that both LIPUS and PEMF improved the healing index and decreased the amount of time needed to consolidate regenerate bone and remain in fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Urita et al reported improved radiographic bone healing in forearm shortening procedures stabilized with a bone plate and screws. In addition to studies evaluating healing with stabilized osteotomies, others have reported improvement in bone healing with LIPUS treatment for stable fractures …”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses and reviews in the human literature have found that bone healing is most accelerated when LIPUS is used to manage fresh fractures in older patients, with a comminuted configuration . The most recent meta‐analysis by Lascelles et al did not find any effect of LIPUS on pain reduction, days to full weight bearing, time to return to work, or number of subsequent surgeries in man. This study focused on clinically relevant outcome measures that would affect patient quality of life and economic impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation